Persistent postarthroplasty knee pain - Rajesh Gupta (Indian Journal of Pain, 2019)
Knee arthroplasty is done to relieve pain. The procedure itself can cause long lasting pain which can significantly decrease the quality of life and mobility. The factors leading to pe rsistent pain relate to patient and surgery and the management of pain before and after the surgery. The management of persistent arthroplasty pain is multidisciplinary and involves conservative and interventional pain medicine.